PROSES PERENCANAAN AKOMODASI UNTUK PEMBICARA DALAM EVENT FOREIGN POLICY CONFERENCE (STUDI KASUS: CIFP 2018) - Baby Bonicha Harmesa; Amirrudin Amirrudin (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2020)
In the conference, accomodation is very important especially for the speakers. Foreign Policy Community of Indonesia is one of foreign relations community in Indonesia who held international conference discussing about foreign policy. One of the most important things on the accomodation process is choosing the hotels, length of stay, category of hotels and reservation itself. We did this because speakers had to get their security and convenience during conference. The aim of this research to acknowledge what the activity has been done during the process of the arrangement accomodation at the activity of the conference itself. The research method used os descriptive qualitative using data taken from related companies.